2012
DOI: 10.1186/1742-2094-9-248
|View full text |Cite
|
Sign up to set email alerts
|

TLR-4 ligation of dendritic cells is sufficient to drive pathogenic T cell function in experimental autoimmune encephalomyelitis

Abstract: BackgroundExperimental autoimmune encephalomyelitis (EAE) depends on the initial activation of CD4+ T cells responsive to myelin autoantigens. The key antigen presenting cell (APC) population that drives the activation of naïve T cells most efficiently is the dendritic cell (DC). As such, we should be able to trigger EAE by transfer of DC that can present the relevant autoantigen(s). Despite some sporadic reports, however, models of DC-driven EAE have not been widely adopted. We sought to test the feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Although we provide evidence that LPS directly stimulates the differentiation of Th17 cells in vitro, it remains to be studied whether LPS works directly on Th17 differentiation or indirectly via APC in vivo, as previously reported [3][4][5].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although we provide evidence that LPS directly stimulates the differentiation of Th17 cells in vitro, it remains to be studied whether LPS works directly on Th17 differentiation or indirectly via APC in vivo, as previously reported [3][4][5].…”
Section: Discussionmentioning
confidence: 78%
“…LPS either inhibits or stimulates the induction of EAE by regulating antigen presenting abilities of dendritic cells [4,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several experimental and human studies have suggested a potential role of Toll‐like receptors (TLRs), molecular components that regulate the innate immune system, in the induction and perpetuation of inflammation in autoimmune diseases . Specifically, the cell surface Toll‐like receptor 4 (TLR4) has been implicated in the development of several experimental and human autoimmune disorders, including experimental autoimmune encephalomyelitis, systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis, type 1 diabetes, and multiple sclerosis …”
Section: Introductionmentioning
confidence: 99%